Q: What is the simplified expression for 2a2b a2 5ab 3ab2 b2 2a2b 2ab?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

Related questions

let binomial be (a + b)now (a+b)3 will be (a+b)(a+b)2 = (a+b)(a2 + 2ab+ b2) = a(a2+ 2ab+ b2) + b(a2 + 2ab+ b2) = a3+ 2a2b+ ab2 + a2b + 2ab2 + b3 = a3+ 2a2b+ ab2 + a2b + 2ab2 + b3 = a3 +3a2b + 3ab2 +b3 hope it helped... :D

It is an expression

( 2ab ) is.

Well, isn't that just a happy little math problem we have here? To factorise 4ab - 6ab, we can first factor out the common factor, which is 2ab. So, we have 2ab(2 - 3) or simply 2ab(-1). And just like that, you've simplified the expression beautifully!

-2ab

An expression.

a2b2 - 2ab - 25 is a quadratic expression in the variables ab. There is no equation or inequality in the question so there is nothing that can be solved. Because of the nature of the expression a and b cannot be separated in any meaningful way.

Algebraically:((a+b) / 2) / ((a+b) / (2ab)) = 2ab(a + b) / 2(a + b) = (2a2b + 2ab2) / (2a + 2b) = abAs an example, let a = 2 and b = 3 then:i) (a + b) / 2 = (2 + 3) / 2 = 5/2ii) (a + b) / (2 * a * b) = (2 + 3) / (2 * 2 * 3) = 5 / 12Therefore i) is ab times larger than ii). (for these specific example numbers it will be 6 times larger)

The given terms can be simplified to: a -b

(2a + 3)(b - 3c)

2ab-2 = 0

2ab-6bc = -4